MAINTAINING ECONOMIC STABILIZATION IN INDONESIA AND SOUTH KOREA THROUGH DIGITAL FARMING - Christianawati, Aprillia (Journal of Environmental Science and Sustainable Development, 2019)
Digital farming is a type of digital economy that cannot be separated from essential elements, such as data availability and farmers themselves. Digital farming is found easily in many developed or agricultural countries, such as southern Europe and Brazil, nor to Indonesia and South Korea. However, Indonesia and South Korea experienced internet utilization and agricultural land area discrepancies which come to similar result, still developing sustainable agriculture. Thus, subjects of the study are Indonesia and South Korea due to their location in the Asian continent and similar history as developing countries in the past. Using farmer households and land agricultural data from Central Bureau of Statistics Indonesia and Statistics Korea, this study conducts quantitative analysis through fuzzy analysis and qualitative analysis through charts and explorative study. Based on quantitative analysis, the results are suitability maps between agricultural land area and farm households in Indonesia and South Korea due to agricultural land area, especially rice field, and farm households are the variables. Meanwhile, qualitative analysis produces charts and descriptive explanations, including internet utilization from World Bank. The rice field area is linked to land conversion, whilst farm household populations are linked to the prosperity of farmers. Indonesia has more farm households and rice field areas than South Korea, but South Korea has the technology to boost productivity and efficiency. The mutual relationship can be built by seeing food security in South Korea and digital farming implications in Indonesia. Therefore, both countries could strengthen bilateral relations beside of digital farming actualization.